2003
DOI: 10.1159/000074244
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Short Stature: Influence of Each Parent’s Height on Clinical-Biological Features

Abstract: Idiopathic extremely short stature probably has several causes. Objective: To evaluate the influence of each parent’s height on clinical-biological features. Methods: 57 patients without intrauterine growth retardation seen at 7.9 ± 0.4 years for height ≤–3 SD were classified according to the difference between their target height and actual height: <2 SD in familial short stature (FSS, n = 28) and >2 SD in non-FSS (n = 29). Results: Height decreased from –0.5 ± 0.1 SD at birth to –2 ± 0.2 SD at 1 year and –2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Small maternal height is a wellknown risk factor for poor height gain in a normal population. 21 This obviously also holds true for moderately preterm-born children. It was surprising that we found that in moderately preterm-born children short lengths of mothers were also associated with poor weight gain, albeit less strongly so than poor height attainment.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Small maternal height is a wellknown risk factor for poor height gain in a normal population. 21 This obviously also holds true for moderately preterm-born children. It was surprising that we found that in moderately preterm-born children short lengths of mothers were also associated with poor weight gain, albeit less strongly so than poor height attainment.…”
Section: Discussionmentioning
confidence: 93%
“…Factors in the latter category for the child were GA, SGA, gender, in vitro fertilization/intracytoplasmic sperm injection, part of a multiple birth, and breastfeeding during the first 6 months of life, and factors for the mother were height, age, ethnicity, level of education, smoking during pregnancy, and family income. 10,[21][22][23][24] Data from appropriate-for-GA (AGA) children were also analyzed separately to clarify any differences between AGA and SGA children. All analyses were performed with SPSS 16 for Windows (SPSS Inc, Chicago, IL).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of short stature at the end of growth demonstrates that parental height has a significant effect on this outcome, confirming the similarity of these groups regarding familial inheritance of growth 8,19,[21][22][23] . The two methods of assessment of final height, BayleyPinneau and TW3, did not show good agreement when used to predict final height.…”
Section: Methodsmentioning
confidence: 61%
“…35,36 In extremely short children with ISS born AGA (n ϭ 28), there was a higher percentage of short fathers than mothers, and fathers' height SDS was positively correlated with the children's height SDS at first clinical presentation. 21 Other findings point to a maternal factor because extremely short children with familial short stature born SGA showed a positive correlation between target height and maternal height. Unfortunately, there was no clear distinction between the genders.…”
Section: Discussionmentioning
confidence: 99%